Joint Audit and Tax Fraud: Case of Listed American Companies - Hamza Ben Said; Salma Damak Ayadi; Feten Arfaoui (Journal of Accounting and Management Information Systems (JAMIS), 2025)
Research Question: How does the presence of joint auditors impact tax evasion practices in publicly traded U.S. companies, and what role does audit committee expertise play in mitigating tax evasion? Motivation- The motivation for this study stems from the desire to understand the potential role of joint auditing and the expertise of audit committees in reducing tax evasion among U.S. publicly traded companies. The research is grounded in agency theory and stewardship theory to explore how governance mechanisms influence corporate tax behaviour. Idea: The central idea of the study is that joint auditing, as well as stronger audit committees with greater expertise, may reduce the likelihood of tax evasion. By examining these factors, the study aims to determine if joint audits serve as a deterrent to tax evasion and if audit committee expertise has a significant effect on corporate tax practices. Data: The study uses a dataset comprising 225 observations from 27 publicly traded U.S. companies. This dataset provides the necessary data to explore the relationship between joint auditing, audit committee expertise, and tax evasion. Tools: Binary logistic regression is used to analyse the dataset, enabling the study to assess the relationship between joint auditing and the likelihood of tax evasion. This statistical method helps determine the significance of these relationships within the dataset. Findings: The results of the study indicate that U.S. companies listed on stock exchanges with joint auditors are significantly less likely to engage in tax evasion, suggesting that joint auditing may act as a deterrent. Furthermore, a significant negative correlation is found between the expertise of the audit committee and the incidence of tax evasion, indicating that stronger audit committees are associated with lower rates of tax evasion. Contribution: This study contributes to the literature by providing evidence of the effectiveness of joint audits and proficient audit committees in mitigating tax evasion. The findings offer valuable insights for regulatory bodies and corporate governance practices, suggesting that both joint auditing and enhanced audit committee expertise may help reduce tax evasion in publicly traded companies.
Keywords: M5; M21; 650; Cο-auditors; tax evasion; audit committee expertise; listed American companies